The Nestle Share Price Dynamics Analysis and Forecasting - Dzerjinsky, Roman I. (Software Engineering Application in Informatics, 2021)
The article presents the latent periodicities’ study results in the Nestle shares dynamics using anamorphosis for the Gompertz models. The self-similar growth ranges boundaries are interconnected with the functions local minimums and together with them determine the world prices spectral composition for Nestle shares. The series structural analysis showed the growth possibility in the shares’ value until 2025, and after reaching its global maximum at the 2025 end, its fall and reaching its minimum in the 2026 third quarter. The development unstable phase (the restructuring phase) falls on the period from 2028 to 2037. #COMESYSO1120.